BERBAGAI BERKAH BID’AH NYADRAN DALAM BUDAYA ISLAM JAWA - Daryono Daryono (Jurnal Dinamika Sosial Budaya, 2017)
This study aims to understand the notion of bid'ah with technical implementation, especially how to send the deceased's prayer in Javanese Islamic culture called nyadran with various blessings (reward) and moral values. This type of research is library research. The source data is, various hadith of the Prophet Muhammad saw and various works of experts both clarify the moral values of Javanese Islamic culture and about nyadran with various blessings. The method of analysis is, content analysis with sociological approach whose model is sociological interpretation. The results of this study provide an understanding of the meaning, type and law of heresy especially commemorating death as a way of sending prayers called nyadran in Javanese Islamic culture. Through the understanding is expected to be used as a reference of the appropriate implementation of his time.